Accounting for carbon emission rights: China’s experience - M. A. Amurskaya (Учёт. Анализ. Аудит, 2023)
The article is devoted to the modern Chinese experience in accounting for carbon rights in the context of the active implementation of low-carbon economic development practices both at the national and international levels. The methodological basis of the work is the main regulatory legal acts of the People’s Republic of China that regulate the accounting of rights to carbon emissions and carbon trading, scientific research by Chinese authors on the main problems and tasks of national accounting of carbon rights, accounting practices of key Chinese enterprises in the energy sector. On this basis, the main theoretical aspects of accounting for rights to carbon emissions are highlighted, which are the subject of active scientific discourse in China at the present stage: the goals of carbon accounting, subject affiliation, features of information disclosure. Based on the main provisions of current regulations and an analysis of the accounting practices that have developed over the past 7 years of key Chinese enterprises in the industry, the modern accounting practices of carbon rights and financial reporting disclosures are presented in a concise form: metric properties, main involved accounts of the National Chart of Accounts of China, information to be disclosed in the notes to the financial statements. The study is crowned by the identified main problems of the modern Chinese practice of accounting for carbon rights in an aggregated form and the proposals formulated by the author. The results of the work contribute to the theory of low-carbon accounting, more specifically, the approaches of scientists are presented, and also provide the Russian reader with the opportunity to get acquainted with the accounting practice of carbon rights in China — in the country that makes the most significant “contribution” to the processes of environmental pollution in the global scale. The the author’s reliance on on authentic sources in Chinese is of particular value to the work, which reveal the thoughts, ideas, practices that are inaccessible to a wide range of readers.